Numerical Modeling in Civil and Mining Geotechnical Engineering - Li, Li (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue (SI) collects fourteen articles published by leading scholars of numerical modeling in civil and mining geotechnical engineering. There is a good balance in the number of published articles, with seven in civil engineering and seven in mining engineering. The software used in the numerical modeling of these article varies from numerical codes based on continuum mechanics to those based on distinct element methods or mesh-free methods. The studied materials vary from rock, soil, and backfill to tailings. The investigations vary from mechanical behavior to hydraulic and thermal responses of infrastructures varying from pile foundations to tailings dams and underground openings. The SI thus collected a diversity of articles, reflecting the state-of-the-art of numerical modeling applied in civil and mining geotechnical engineering.